2013
DOI: 10.1111/jam.12218
|View full text |Cite
|
Sign up to set email alerts
|

Weissellicin L, a novel bacteriocin from sian-sianzih -isolated Weissella hellenica 4-7

Abstract: Aim: To identify and characterize novel bacteriocins from Weissella hellenica 4-7. Methods and Results: Weissella hellenica 4-7, isolated from the traditional Taiwanese fermented food sian-sianzih (fermented clams), was previously found to produce a bacteriocin active against Listeria monocytogenes and some other Gram-positive bacteria. Bacteriocin activity decreased slightly after autoclaving (121°C for 15 min), but was inactivated by protease K and trypsin. Mass spectrometry analysis revealed the bacteriocin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…Weissellicin 110, produced by W. cibaria 110 was active against several LAB, including Lactobacillus, Leuconostoc and Weissella species [117]. Several other bacteriocins have been purified from W. hellenica strains (weissellicins D, L, M, Y, 7293A and 7293B) and W. paramesenteroides (weissellicin A) [114,[160][161][162][163]. Weissellicin L presented a high homology with leucocin B-TA33a, produced by Lc.…”
Section: Production Of Antimicrobial Substancesmentioning
confidence: 99%
“…Weissellicin 110, produced by W. cibaria 110 was active against several LAB, including Lactobacillus, Leuconostoc and Weissella species [117]. Several other bacteriocins have been purified from W. hellenica strains (weissellicins D, L, M, Y, 7293A and 7293B) and W. paramesenteroides (weissellicin A) [114,[160][161][162][163]. Weissellicin L presented a high homology with leucocin B-TA33a, produced by Lc.…”
Section: Production Of Antimicrobial Substancesmentioning
confidence: 99%
“…The closest relative is weissellicin L from Weissella hellenica 4e7. The 17-aa determined N-terminal sequence of weissellicin L shares 88% identity with leucocin B [15]. L. mesenteroides subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Many bacteriocins show great inhibitory ability against food pathogens and therefore attract special interest (Klaenhammer 1988 ; Ennahar et al 1999 ; Cleveland et al 2001 ; Yang et al 2014 ). In the previous studies, we reported that Weissella hellenica 4 – 7, isolated from the traditional Taiwanese fermented food sian-sianzih (fermented clams), is capable of producing a novel bacteriocin, termed weissellicin L (Leong et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%